2021
DOI: 10.2166/wst.2021.419
|View full text |Cite
|
Sign up to set email alerts
|

Organic matter parameters in WWTP – a critical review and recommendations for application in activated sludge modelling

Abstract: This paper includes a comprehensive literature review of sludge composition data from wastewater treatment plants. 722 data sets from 249 sources were used to establish typical ratios between COD and solids-based parameters and to verify rule-of-thumb values, respectively. Confirmation of these typical ratios can also be accomplished by using biochemical composition data. It is shown that a correlation between data from proteins, lipids and carbohydrates analysis can be related to COD/VSS ratios. Finally, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 47 publications
(47 reference statements)
1
8
0
Order By: Relevance
“…A strong linear relationship between COD and TSSs was found with an R 2 of 0.81, as shown in Figure 3 . This finding was similar to other researchers’ work [ 35 , 36 ]. One study has found multiple regression among TSSs and COD, pH and total dissolved solids for the removal of solids from chemically enhanced primary treatment systems of wastewater [ 37 ].…”
Section: Resultssupporting
confidence: 94%
“…A strong linear relationship between COD and TSSs was found with an R 2 of 0.81, as shown in Figure 3 . This finding was similar to other researchers’ work [ 35 , 36 ]. One study has found multiple regression among TSSs and COD, pH and total dissolved solids for the removal of solids from chemically enhanced primary treatment systems of wastewater [ 37 ].…”
Section: Resultssupporting
confidence: 94%
“…[ 27,28 ] In most studies, the ratios vary from 0.9 to 2 and are typically based either on an empirical formula or on observed values for raw sewage (i.e., 1.6 for biodegradable matter). [ 27,28 ] Ahnert et al. reported that according to experimental and theoretical considerations, the TCOD/VS ratios range from 2 to 2.9 for lipids, 1.4 to 1.5 for proteins, and 1.07 to 1.18 for carbohydrates.…”
Section: Resultsmentioning
confidence: 99%
“…The overall ratio of TCOD/VS indicates the contribution of various components, that is, biodegradable matter, inorganic matter, biomass, and endogenous decay products, to PM. [27,28] In most studies, the ratios vary from 0.9 to 2 and are typically based either on an empirical formula or on observed values for raw sewage (i.e., 1.6 for biodegradable matter). [27,28] Ahnert et al reported that according to experimental and theoretical considerations, the TCOD/VS ratios range from 2 to 2.9…”
Section: Pig Manure Characterizationmentioning
confidence: 99%
“…BMPs were set up in 200 mL glass serum bottles with crimp caps and septum seals. In Phase I, the substrate to inoculum ratio (S/I) was set at 2.5 g COD/g VSS based on prior studies [19,27,28]. The yeast-only system in Phase 1 soured due to volatile fatty acid (VFA) accumulation.…”
Section: Methodsmentioning
confidence: 99%